Increasing Prevalence and High Risk of Associated Anomalies in Congenital Vertebral Defects: A Population-based Study. Issue 5 (17th May 2022) - Heiskanen, Susanna; Syvänen, Johanna; Helenius, Ilkka; Kemppainen, Teemu; Löyttyniemi, Eliisa; Gissler, Mika; Raitio, Arimatias
Abstract : Background: Congenital vertebral anomalies are a heterogeneous group of diagnoses, and studies on their epidemiology are sparse. Our aim was to investigate the national prevalence and mortality of these anomalies, and to identify associated anomalies. Methods: We conducted a population-based nationwide register study and identified all cases with congenital vertebral anomalies in the Finnish Register of Congenital Malformations from 1997 to 2016 including live births, stillbirths, and elective terminations of pregnancy because of major fetal anomalies. Cases were categorized based on the recorded diagnoses, associated major anomalies were analyzed, and prevalence and infant mortality were calculated. Results: We identified 255 cases of congenital vertebral anomalies. Of these, 92 (36%) were diagnosed with formation defects, 18 (7.1%) with segmentation defects, and 145 (57%) had mixed vertebral anomalies. Live birth prevalence was 1.89 per 10, 000, and total prevalence was 2.20/10, 000, with a significantly increasing trend over time ( P <0.001). Overall infant mortality was 8.2% (18/219); 3.5% (3/86) in patients with formation defects, 5.6% (1/18) in segmentation defects, and 12.2% (14/115) in mixed vertebral anomalies ( P =0.06). Co-occurring anomalies and syndromes were associated with increased mortality, P =0.006. Majority of the cases (82%) were associated with other major anomalies affecting most often the heart, limbs, and digestive system. Conclusions: In conclusion, the prevalence of congenital vertebral anomalies is increasing significantly in Finnish registers. Detailed and systematic examination is warranted in this patient population to identify underlying comorbidities as the majority of cases are associated with congenital major anomalies. Level of Evidence: Level III.